Ontology based Clinical Practice Justification in Natural Language - Mendes, David (2014)
One of the most important contributions that any decision support system can make to achieve wide acceptance among any community is to be able to justify its own suggestions. When dealing with highly technical and scientifically advanced practitioners like medical doctors or any other related clinical workers, the ability to justify itself using the domain specialist usual terminology and technicalities is imperative. In this article we demonstrate the use of an ontological framework as inferencing basis for automatic sound clinical suggestions providing. Our work has two main contributions, consolidating the use of \{OGCP\} (Ontology for General Clinical Practice) as foundation and providing controlled English justifications of the extracted suggestions. We found that clinical practitioners feel as acceptable the Attempto Controlled English justifications generated from the knowledge base.